Fused Clitoral Hood Presenting as a Periclitoral Mass. Issue 6 (2nd December 2022) - Maybury, Edward K.; Recio, Fernando O.; Ahmad, Sarfraz; McKenzie, Nathalie D.
Abstract : A fused clitoral hood can trap sebaceous material, which can accumulate over time, presenting similarly to benign and malignant periclitoral masses. Abstract : BACKGROUND: Periclitoral masses are seldom reported. One cause is a congenitally fused clitoral prepuce (or clitoral hood). CASE: A patient was referred to our gynecologic oncology practice with a suspicious periclitoral mass for evaluation of possible malignancy. The clitoral hood was, in fact, fused such that the glans was completely covered. Surgical excision of the distal prepuce (or clitoral hood) expelled trapped sebaceous material and revealed a normal-appearing glans clitoris. Clitoral hood reconstruction restored the patient's external genitalia to normal anatomy. CONCLUSION: Fused clitoral prepuce causing trapped sebaceous material can mimic an expanding periclitoral mass and should be considered in the differential diagnosis.